Modification of strut effectiveness factor for reinforced concrete deep beams strengthened with CFRP laminates - Panjehpour, Mojtaba; Abang Ali, Abang Abdullah; Voo, Yen Lei; Abd Aziz, Farah Nora Aznieta (Consejo Superior de Investigaciones Cientificas (C S I C), 2014)
This paper proposes a method to modify the strut effectiveness factor in the strut-and-tie model for CFRP-strengthened reinforced concrete deep beams. Two groups of deep beams comprising six ordinary reinforced concrete deep beams and six CFRP-strengthened reinforced concrete deep beams were experimentally tested under the four-point bending configuration. The shear span-to-effective depth ratio of the beams in each group was 0.75, 1.00, 1.25, 1.50, 1.75, and 2.00. The theoretical principal tensile strain in CFRP-strengthened struts was modified based on a proposed empirical relationship, based on two ratios: the experimental to the theoretical value of principal tensile strain and the shear span-to-effective depth of deep beams.